2019
DOI: 10.3390/atmos11010009
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Air Pollution and All-Cause Mortality in Singapore

Abstract: Ambient air pollution is a risk factor for both acute and chronic diseases and poses serious health threats to the world population. We aim to study the relationship between air pollution and all-cause mortality in the context of a city-state exposed to the Southeast Asian haze problem. The primary exposure was ambient air pollution, as measured by the Pollutants Standards Index (PSI). The outcome of interest was all-cause mortality from 2010–2015. A time-stratified case-crossover design was performed. A condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The results of a study by Kunzli et al [15] showed that, in European countries like Austria, France, and Switzerland, air pollution is the cause of death of more than 40,000 people. As well, previous studies in Southeast Asia demonstrated a significant association between an increase in mortality and Pollutants Standards Index [16][17][18][19][20]. Likewise, trends in low birth weight, neonatal deaths, fetal and infant mortality, spontaneous abortion, and the occurrence of birth defects were found to correspond closely with quantities of outdoor pollution [21][22][23][24][25].…”
Section: Introductionsupporting
confidence: 74%
“…The results of a study by Kunzli et al [15] showed that, in European countries like Austria, France, and Switzerland, air pollution is the cause of death of more than 40,000 people. As well, previous studies in Southeast Asia demonstrated a significant association between an increase in mortality and Pollutants Standards Index [16][17][18][19][20]. Likewise, trends in low birth weight, neonatal deaths, fetal and infant mortality, spontaneous abortion, and the occurrence of birth defects were found to correspond closely with quantities of outdoor pollution [21][22][23][24][25].…”
Section: Introductionsupporting
confidence: 74%
“…Furthermore, our solution is a preliminary take on this problem in Singapore, and it predicts the demands only under certain typical conditions. Although there are peaks and troughs in demands every now and then, these values are in no way near the extremes that happen during very large-scale incidents, e.g., epidemics, haze [33][34][35], and diurnal temperature changes. A potential area of improvement is to make use of historical data to model the demand at such extreme cases of large-scale incidents.…”
Section: Discussionmentioning
confidence: 97%
“…Among the 70 studies, 42, 11, and 15 were EPI, HBE and HRA studies, respectively; two were both EPI and HBE. Forty-nine studies were conducted in the maritime area (Indonesia [ 41 , 44 57 ], Malaysia [ 29 , 58 68 ], Singapore [ 69 82 ], Brunei [ 83 , 84 ], multiple countries in maritime area [ 40 , 85 89 ]), 17 in the mainland area (Thailand [ 32 , 90 104 ], multiple countries in mainland area [ 105 ]); and 4 in multiple countries in the entire Southeast Asia [ 19 , 106 108 ] ( Fig 2 ). The breakdown of studies by country is as follows: 41 EPI [ 32 , 44 46 , 49 58 , 61 67 , 69 , 70 , 75 84 , 90 , 97 103 ], three HBE [ 41 , 47 , 104 ], and 15 HRA [ 29 , 48 , 59 , 60 , 68 , 71 74 , 91 96 ] studies were conducted in a single country (Indonesia, Malaysia, Singapore, Brunei, and Thailand); whereas one EPI study [ 85 ], eight HBE […”
Section: Resultsmentioning
confidence: 99%